Performance of Kharif Onion in Vindhyan Region of Madhya Pradesh (Indian Journal of Extension Education, 2011)
A field study was conducted at the farmer’s field in Rewa district (M.P.) during kharif season of 2008- 09 to 2011-12 on Kharif Onion c.v. agrifound darked. Observation was recorded on number of leaves per plant, plant height, neck-thickness, length and width of bulbs, length: width of bulbs, bolting percentage, weight of bulb and bulb yield (q/ha). The results showed a significant difference on number of leaves per plant, plant height, neck-thickness, length and width of bulbs, length: width of bulbs, bolting percentage, weight of bulb and bulb yield. The maximum plant height (42.60 cm), number of leaves per plant (11.0), length of bulb (5.80 cm), width of bulb (8.07 cm), weight of bulb (85.40 g) and bulb yield (265.83 q/ha) were recorded in F5 and the highest nick thickness (0.90 cm) in F8, length: width of bulb (0.75) in F3 and bolting percentage (5.7%) were observed in F7. However, the minimum plant height (38.97 cm), number of leaves per plant (9.0), length of bulb (4.60 cm), width of bulb (7.0 cm), weight of bulb (72.70 g) and bulb yield (245.77 q/ha) were recorded in F7 and the minimum nick thickness (0.70 cm) in F1 and length: width of bulb (0.65) were noted in F4. The difference in yield parameter was attributed to the management practices followed by the selected farmers.